2001
DOI: 10.1159/000051279
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Dementia Care: Functional Status over Time of Persons with Alzheimer Disease in a Residential Care Centre Compared to Special Care Units

Abstract: Residential care centres (RCCs) for persons with Alzheimer disease are increasing worldwide, but there are few studies that compare the functional outcomes of RCC residents to residents of other types of continuing care settings. This study compared residents of the first Canadian RCC on physical, cognitive, behavioural and emotional functioning 6, 12 and 18 months after admission to residents of special care units (SCUs) operated by the same continuing care provider. SCU residents were initially functioning l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 12 publications
0
30
0
Order By: Relevance
“…A greater global cognitive impairment in the SCU group was found in 10 studies with large [33,38,39,42], moderate [20,28,36] and small effect sizes [21,34] or significant p values [43]. In contrast, 1 study showed an increased cognitive impairment with a large effect size in a limited number of participants [35], and 1 study showed a moderate effect size in a younger n-SCU patient group [9].…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…A greater global cognitive impairment in the SCU group was found in 10 studies with large [33,38,39,42], moderate [20,28,36] and small effect sizes [21,34] or significant p values [43]. In contrast, 1 study showed an increased cognitive impairment with a large effect size in a limited number of participants [35], and 1 study showed a moderate effect size in a younger n-SCU patient group [9].…”
Section: Resultsmentioning
confidence: 81%
“…In 1 of them, the calculated effect size at baseline was nil for social activities such as going to the barber and social withdrawal [32], and in another paper, no significant p value was found for participation in pleasant events and social withdrawal [14]. Two studies showed large [38] or small [20] effect sizes, implying that patients living in the SCU showed a better psychosocial function compared to n-SCU patients. One study [15] showed a moderate effect size, indicating a distinct psychosocial behavior in a small patient population from a small-scale, homelike SCU compared to patients from an n-SCU.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Special Care Facility: Reimer et al, 2004;Slaughter et al, 2006. "Woodside": Arehart-Treichel, 2001;Danes, 2002;Janzen, 2000;McAllister and Silverman, 1999;Nagy, 2002;Saxton et al, 1998;Warren et al, 2001;2002. ADL = activities of daily living; CPS = Cognitive Performance Scales; GDS = Global Deterioration Scale; MDS = minimum data sets; MMSE = Mini-mental State Examination.…”
Section: Residents' Characteristicsmentioning
confidence: 99%